TOOLS FOR ANTI-SYSTEMIC CORRUPTION: ASPECTS OF ECONOMIC SECURITY OF BUSINESS - VASYLTSIV, Taras; BARAN, Rostyslav (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The study revealed the relevance of the issue of the formation and implementation of the state anti-corruption policy as a critical negative factor in ensuring the economic security of entrepreneurship in the country. The purpose of the study is to identify the tools for combating systemic corruption in Ukraine and to strengthen a number of important parameters of the economic security of entrepreneurship due to this. It was concluded that despite a number of positive changes, systemic corruption has still not been overcome. Systemic corruption is proposed to be understood as corrupt actions in the system of state authorities, associated with large volumes of operations and when corruption has turned into a system characterized by: a set of interconnected elements, the presence of two or more types of connections, the existence of hierarchical levels of corruption, self-organization and reproducibility of corruption and related processes. Systemic corruption gives rise to corresponding systemic negative consequences, one of which, of course, is demotivation to entrepreneurship, respectively, a critical decline in business activity of the population, and, therefore, competition in the markets, investments, employment, etc. It has been proven that the policy of combating systemic corruption should be systemic and based on a set of tools aimed at correcting the situation at all levels of relations, types of economic activity and time horizons. The effective implementation of the applied principles of the state policy of decriminalization of the national economy requires the design of an organizational and economic mechanism for combating systemic corruption, especially in the basic types of economic activity, which is positioned as a regulator of negative economic processes, the functioning of which is aimed at observing the principles of transparency in business and government relations, the absence of bribery, the legalization of shadow capital, reducing the scale of the circulation of shadow tools, increasing the transparency of management and overcoming the disparity between the amount of tax revenues and the real scale management of subjects of the national economy.
Keywords: systemic corruption; economic security of business; anti-corruption mechanism; tools for strengthening economic security; business entities